(untitled) (Al-Qamar, 2022)
The life of the Messenger of Allah ﷺ is related to the entire humanity. This is the reason that much has been written on the life and biography of Prophet Muhammad (peace be upon him). From the beginning, the authors of the biography have written in different ways on the biography of Prophet Muhammad (peace be upon him). It has always been the dream of every Muslim to have the honor of writing the biography of his Prophet. No one can compete with this pride of Muslims until the Day of Judgment that they preserved every word of the circumstances and events of their Prophet with the inquiry that no one The conditions of the person have not been recorded with such comprehensiveness and care till date and cannot be done in the future. Not only Muslims, but also non-Muslims are seen in praise and description of the Prophet (peace and blessings of Allah be upon him) and mention of him. For Muslims, the study of biographies is not just an academic awareness, but an important religious necessity, while the nature of biographical studies for non-Muslims may be somewhat different. His (peace and blessings of Allah be upon him) achievements are very interesting and surprising for historians. Those non-Muslims who have hatred and hatred against Islam and the Prophet of Islam, the purpose of studying their biography is to gain awareness of the real facts and distort and present the same events and present these events in their own color contrary to the reality. Despite all this, the most written and read in the world with reference to the biography of Muhammad, the Messenger of Allah, and this is an impressive fact, In this article, the light of ancient and modern sources of biography have been reviewed.